ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA DALAM MENYELESAIKAN SOAL CERITA GEOMETRI - Agustina, Agustina; Andryani, Sulis; Zulkarnain, Zulkarnain (IAIN Pontianak, 2024)
This study aims to analyze student’s ability to solve story problrms in Geometry based on predetermined indicator. The method used inthis research is a descriptive qualitative approach. The seventh grade students of Madrasah Al-Mubarak Miftahul Ulum were 33 students as research subjects. Techniques in data processing using descriptive statistics. Data collection unes measurement techniques in the form of essay tests. Based on the results and discussion, it is stated that only 40% of students can write what they know, 25% of students can write down what is asked, 0.40% students can determine formulas and enter values and 0% of students cannot calculate and make solutions to story problems. This identified that the seventh grade students of Madrasah Al-Mubarak Miftahul Ulum had difficulties in solving story problrms on geometry material.